UP diksiyonaryong Filipino - Almario, Virgilio S. 1944-.; University of the Philippines. Sentro ng Wikang Filipino (Quezon City UP Sentro ng Wikang Filipino, 2010)
Filipino language dictionary.
Definitions in Tagalog, with entries in several languages of the Philippines.
Keywords: Filipino language -- Dictionaries -- Polyglot; Filipino language -- Dictionaries